2008
DOI: 10.5194/angeo-26-185-2008
|View full text |Cite
|
Sign up to set email alerts
|

Multi-instrument observations of a large scale Pc4 pulsation

Abstract: Abstract. On 7 November 2005 various ground based and spaced based instruments registered five wave packets with frequencies in the Pc4 range. The most prominent of the five wave packets was observed in ground based magnetometer data spanning almost all latitudes on the dayside magnetosphere. The propagation from the dayside into the tail is deduced from Poynting flux calculations of Cluster data and an onset time analysis of the ground based magnetometer data. This suggests an upstream source. Backstreaming i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…The density changes by about 2 orders of magnitude. The band‐pass‐filtered magnetic field magnitudes shown in Figure (middle row) reveal the bursty nature of the observed wave activity, which is in agreement with observations of upstream waves penetrating into the inner magnetosphere [ Clausen et al , , ]. Two wave bursts were observed, one prior to the plasmapause crossing and one afterward.…”
Section: Observationssupporting
confidence: 87%
See 1 more Smart Citation
“…The density changes by about 2 orders of magnitude. The band‐pass‐filtered magnetic field magnitudes shown in Figure (middle row) reveal the bursty nature of the observed wave activity, which is in agreement with observations of upstream waves penetrating into the inner magnetosphere [ Clausen et al , , ]. Two wave bursts were observed, one prior to the plasmapause crossing and one afterward.…”
Section: Observationssupporting
confidence: 87%
“…Another way of using MHD waves, albeit at much lower frequencies, to identify the plasmapause is described in Menk et al [] who study the latitudinal variation of magnetic field line eigenfrequencies using closely spaced ground‐based magnetometers. In the case of field line eigenfrequencies, the wave period is dependent on the Alfvén velocity along the magnetic field line [e.g., Cummings et al , ], and hence, a sudden change in plasma density results in a sudden change of the observed eigenfrequency [ Menk et al , ; Clausen et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…The equatorial plane location and the magnetic field values for the Alfvén velocities came from the T96 model using disturbance storm time index DST = 2.5 nT, SW dynamic pressure p = 1.4 nPa, IMF B y = 3.5 nT GSM, and IMF B z = −0.5 nT GSM. Particle density was determined using THM-D measurements and a R −3 dependence from the center of the Earth [Clausen et al, 2008]. This results in a total transit time of 80 s. The observed first pulsation maximum at THM-D occurred at 0437:14 UT while the corresponding first maximum at BKS occurred at 0438:32 UT, giving an observed transit time of 78 s. This agrees well with our estimate.…”
Section: Discussionsupporting
confidence: 83%
“…It has commonly been found that eigenfrequencies decrease with increasing magnetic latitude (e.g., Baransky et al, 1989;Clausen et al, 2008;Samson et al, 1971;Wharton et al, 2018). This has been attributed to the lengthening of the field lines toward the magnetic poles.…”
Section: Variations With Geomagnetic Latitude and Mltmentioning
confidence: 99%